Analisis Pengaruh Penanaman Modal Asing, Pendapatan Asli Daerah dan Indeks Pembangunan Manusia Terhadap Ketimpangan Wilayah di Provinsi Sumatera Barat - mohd syafiq; Maizul Rahmizal (Media Riset Ekonomi Pembangunan (MedREP), 2026)
Regional inequality is a common phenomenon in the economy, arising from variations in the quality of natural resources and demographic conditions in each region. Inequality in West Sumatra showed a significant increase between 2007 and 2023. This study aims to determine whether the variables of Foreign Investment, Regional Original Income, and the Human Development Index have an influence on Regional Inequality in West Sumatra Province. The method used in this analysis is multiple linear regression. The type of data analyzed is secondary data compiled by BPS (Central Statistics Agency) in the form of a time series. From the results that have been studied, it is revealed that the variables of Foreign Investment, Regional Original Income, and the Human Development Index show a positive influence, but do not have a significant impact on regional inequality in West Sumatra Province